2010
DOI: 10.31260/repertmedcir.v19.n2.2010.586
|View full text |Cite
|
Sign up to set email alerts
|

Biología, patobiología y bioclínica de la homocisteína eh la especie humana

Abstract: La homocistinuria fue descrita en 19a2 en niños con dificultades de aprendizaje y en 19a9 McCully informó la evidencia en autopsias de trombosis arterial eztensa y aterosclerosis en niños con elevadas concentraciones de homocisteína plasmática y homocistinuria. La homocisteína, un aminoácido de azufre, es un metabolito intermedio de la metionina, y sobre la base de estos hallazgos bioquímicos, ellos propusieron que la homocisteína plasmática elevada puede causar lesión neural y enfermedad vascular aterosclerót… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Vitamin C prolonged treatment showed anti-inflammatory effect with reduced reactive oxygen and nitrogen species, increasing the bioavailability of NO and inhibing the formation of peroxynitrite. The L-ascorbic acid donates two electrons from a double bond between carbons at positions 2 and 3, this action would preserve the physiological functions of NO by intracellular superóxide ion chelation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C prolonged treatment showed anti-inflammatory effect with reduced reactive oxygen and nitrogen species, increasing the bioavailability of NO and inhibing the formation of peroxynitrite. The L-ascorbic acid donates two electrons from a double bond between carbons at positions 2 and 3, this action would preserve the physiological functions of NO by intracellular superóxide ion chelation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies revealed that rosmarinic acid is bounded to the hyaluronidase binding pocket with four binding interactions [52]. In our study, the hyaluronidase used was not human but bovine, but these are highly phylogenetically conserved proteins [53]. Another compound that has been tested in silico against collagenase, elastase, and tyrosinase enzymes is caffeine, which was shown to form a stable protein-ligand complex validated by molecular dynamics simulation.…”
Section: Discussionmentioning
confidence: 75%